The Mindful Caregiver: Finding Ease in the Caregiving Journey - Kriseman, Nancy L. (Rowman & Littlefield Publishers, 2014)
Caregiving can be enormously challenging, terrifically rewarding, and potentially draining. Caregivers often wonder how they will navigate the tumultuous waters of caregiving and not lose themselves completely. The Mindful Caregiver highlights two major approaches to help transform the journey: adopting a practice of mindfulness, which helps caregivers become more self-aware and fully present with the person with whom they are caring, and honoring “the spirit-side” of caregiving which offers new ways of connecting to one another. These approaches take into account not just the needs of the care recipient, but also the needs of the caregiver and other people in his/her life. Remembering to care for oneself when someone else is in great need can be difficult, but with the suggestions and tips in this book, any caregiver can cultivate routines and practices that benefit everyone. Solutions that caregivers can use in their day to day routines are provided, so caregivers who use them can feel more empowered and hopeful. Using real stories throughout, Nancy Kriseman offers self-care exercises and addresses a wide variety of subjects such as setting realistic expectations, making the best possible decisions, advocating effectively, and evaluating available resources and services. The Mindful Caregiver provides inspiration, encouragement, and guidance for finding ease in the caregiving journey. By emphasizing both mindfulness and the spiritual dimension, caregivers can reap the gifts of caregiving, appreciate the special moments, and find strength during the challenging times.